PEMANFAATAN KOTORAN TERNAK SAPI SEBAGAI SUMBER ENERGI ALTERNATIF RAMAH LINGKUNGAN BESERTA ASPEK SOSIO KULTURALNYA - Rahayu, dkk, Sugi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract The objectives of this activity are: (1) improving knowledge about utilization of biogas from livestock dirt for farmer society and ranchers; (2) giving information about aspect of sosiocultural in utilization of biogas in order to build new businessman; (3) evaluating utilization of prospect of biogas at Jatisarono, Nanggulan, Kulonprogo related to aspect of community development for range longer. The target of this activity is cows ranchers at Jatisarono, Nanggulan, Kulon progo. As for execution methods weared in this activity are experiment, discourse, discussion of information and presentation. The materials are cow livestock dirt for alternative friendly environment fuel, cow livestock dirt energy conversion and aspect sosio cultural of biogas. This activity has been succeeded in understanding and detecting residue utilization of biogas from livestock dirt for farmer society and cow ranchers at Jatisarono. Through this activity, aspect of sosio-cultural of technology biogas in order to build new businessman has been understood by farmer society and cow ranchers at Jatisarono and detect prospect everything that can be developed related to utilization of technology biogas at Jatisarono in order to community development for range longer. Keywords: biogas, sosio cultural, and fuel